Review on the relationship of social capital, absorptive capacity and technology transfer performance: A conceptual framework - Abidin, Rahimi; Abdullah, Che Sobry; Hasnan, Norlena (2012)
The success of technology transfer often depends on many factors.The soft aspects of technology, such as knowledge, skills, and organization, are the critical aspects for the successful transfer of technology.Tacit knowledge and personal experience of an individual can only be obtained in a tacit manner.Therefore social interaction and absorptive capacity are very important to facilitate technological knowledge transfer among the units within an organization.This paper aims to contribute to the existing knowledge in the field of technology transfer by exploring absorptive capacity and an important factor of absorptive capacity that is social capital which may enhance the firms absorptive capacity and technology transfer performance.A conceptual framework synthesized from a review of the literature is presented. The links between variables are viewed by the proposed model.